Perioperative and Long-term Oncological Results of Minimally Invasive Pancreatoduodenectomy as Hybrid Technique – A Matched Pair Analysis of 120 Cases - Deichmann, Steffen; Bolm, Louisa Romina; Honselmann, Kim Christin; Wellner, Ulrich Friedrich; Lapshyn, Hryhoriy; Keck, Tobias; Bausch, Dirk (Zentralblatt für Chirurgie - Zeitschrift für Allgemeine, Viszeral-, Thorax- und Gefäßchirurgie, 2018)
Background Laparoscopic pancreatoduodenectomy is a highly challenging procedure. The aim of this study was to analyse post-operative morbidity and mortality as well as long term overall survival in patients undergoing hybrid LPD, as compared to open pancreaticoduodenecomy (OPD) in a single surgeon series.Methods Patients undergoing pancreatoduodenectomy (PD) in the period from 2000 to 2015 were identified from a prospectively maintained database. All LPD procedures were performed by one specialised pancreatic surgeon (TK). Patients were matched 1 : 1 for age, sex, BMI, ASA, histological diagnosis, pancreatic texture and portal venous resection (PVR). All LPD procedures were performed as hybrid LPD – combining laparoscopic resection and open reconstruction via mini laparotomy.Results A total of 549 patients were identified, including 489 patients in the OPD group and 60 patients in the LPD group. 60 patients were identified who underwent LPD between 2010 and 2015 versus 60 OPD patients operated in the same period. Median overall operation time was shorter in the LPD group than with OPD patients (LPD 352 vs. OPD 397 min; p = 0.002). Overall transfusion units were lower in the LPD group (LPD range 0 – 4 vs. OPD range 0 – 11; p = 0.032). Intensive care unit stay (LPD 1 vs. OPD 6 d; p = 0.008) and overall hospital stay (OHS: LPD 14 vs. OPD 18 d; p = 0.012) were shorter in the LPD groups than in the OPD group. As regards postoperative complications, LPD was associated with reduced rates of clinically relevant grade B/C postoperative pancreatic fistula (LPD 15 vs. OPD 36%; p = 0.036) and grade B/C delayed gastric emptying (LPD 8 vs. OPD 20%; p = 0.049). A total of 56 patients were diagnosed with malignant disease. The number of harvested lymph nodes and R0-resection rates were equal for LPD and OPD patients. LPD patients showed a trend to improved median overall survival (LPD mean 56 months vs. OPD mean 48 months; p = 0.056).Conclusion Hybrid LPD is a safe procedure associated with a reduction in clinically relevant postoperative complications and allows faster recovery. Long term oncological outcome of hybrid LPD for malignant disease is equal to that with the standard open approach.Hintergrund Ziel dieser Studie war es, die postoperative Morbidität und Mortalität sowie Langzeit-Gesamtüberlebensraten bei Patienten nach laparoskopischer Pankreatoduodenektomie (LPD) in Hybridtechnik im Vergleich zur offenen Pankreatoduodenektomie (OPD) anhand der Serie eines LPD-spezialisierten Pankreaschirurgen zu analysieren.Material und Methoden Daten von Patienten, die im Zeitraum 2000 – 2015 eine Pankreatoduodenektomie (PD) erhalten haben, wurden einer prospektiv geführten Datenbank entnommen. Alle LPD-Resektionen wurden von einem Chirurgen (TK) durchgeführt. Es erfolgte ein 1 : 1 Matching der Patienten anhand der Parameter Alter, Geschlecht, BMI, ASA, Histologie, Textur des Pankreasparenchyms und Durchführung einer Pfortaderresektion. Alle LPD-Resektionen wurden in Hybridtechnik mit laparoskopischer Resektion und anschließender Rekonstruktion mittels Minilaparotomie durchgeführt.Ergebnisse Insgesamt konnten 549 Patienten anhand der Datenbank identifiziert werden, 489 Patienten in der OPD-Gruppe und 60 Patienten in der LPD-Gruppe. 60 LPD-Patienten aus dem Zeitraum 2010 – 2015 und 60 OPD-Patienten aus dem Zeitraum 2000 – 2015 wurden in die Studie eingeschlossen. Die mediane Operationszeit in der LPD-Gruppe war verkürzt im Vergleich zur OPD-Gruppe (LPD 352 vs. OPD 397 min; p = 0,002). Die Anzahl perioperativ benötigter Erythrozytenkonzentrate war geringer in der LPD-Gruppe (LPD 0 – 4 vs. OPD 0 – 11; p = 0,032). Die mediane Dauer der intensivmedizinischen Therapie (LPD 1 vs. OPD 6 d; p = 0,008) und die mediane Gesamtdauer des Krankenhausaufenthalts (LPD 14 vs. OPD 18 d; p = 0,012) waren kürzer in der LPD-Gruppe im Vergleich zur offenen Resektion. Die LPD war mit einer geringeren Rate klinisch relevanter Grad-B/C-Pankreasfisteln (LPD 15 vs. OPD 36%; p = 0,036) und verzögerter Magenentleerung Grad B/C assoziiert (LPD 8 vs. OPD 20%; p = 0,049). 56 der eingeschlossenen Patienten wiesen eine maligne Raumforderung auf. Die Anzahl resezierter Lymphknoten und die Rate an R0-Resektionen waren vergleichbar in der LPD- und der OPD-Gruppe. Bei LPD-Patienten zeigte sich der Trend einer verbesserten medianen Gesamtüberlebensrate (LPD 56 vs. OPD 48 Monate; p = 0,056).Schlussfolgerung Die LPD in Hybridtechnik ist eine sichere Technik, die mit der Reduktion klinisch relevanter postoperativer Komplikationen assoziiert ist und eine schnelle postoperative Erholung erlaubt. Die onkologischen Langzeitergebnisse nach LPD in Hybridtechnik bei malignen Befunden sind gleichwertig zur offenen Technik.
Keywords: abdominal surgery; laparoscopic surgery; pancreatic head resection; pancreatic surgery; hybrid laparoscopic pancreatoduodenectomy